Traditional Korean Medicine Usage and Perception: a comparative study between the general population and the disabilities - Ji-Eun Han; Jihye Kim; Kyeong Han Kim; Ji-Yeon Lee; Soo-Hyun Sung (Korean Pharmacopuncture Institute, 2022)
Objectives: This study is a comparative analysis of the satisfaction and recognition characteristics for traditional Korean medicine (TKM) in people with disabilities and the general population of Korea. Methods: Here, 5,000 subjects were categorized into two groups based on a disability rating using the data from the 2017 National Survey for the Usage of Korean Medicine. The relationships among the sociodemographic characteristics, TKM usage status, recognition of TKM usage, and recognition of the effectiveness of the TKM treatment were analyzed based on the disease. The response reliability was verified using the chi-square test analysis method. Results: Disabilities corresponded with low rates of high school or higher education (44%, 83.5%) and no jobs (56.9%, 33.5%), mostly the status of the low-income class with a monthly household income of < 1,500 USD (50.9%, 10.5%), poor health conditions (55.2%, 9.8%), high chronic disease prevalence rate (69.0%, 19.9%), high medical care rate (11.2%, 0.5%), and low commercial health insurance subscription rate (44%, 74.2%). Furthermore, people with disabilities visited TKM institutions more often (88.8%, 74.1%) with a high frequency TKM usage rate of ≥ 1-2 times a month (26.2%, 15.3%). They also reported that the cost of using the TKM was very high (14.7%, 8.8%) and that primarily the application of insurance benefits should be improved (52.6%, 47.5%). The treatment effectiveness for diseases was high for musculoskeletal disorders for both people with disabilities and the general population. Conclusion: Preferential application of insurance benefits for musculoskeletal diseases must be extended to the TKM treatment as well, as people with disabilities have a high recognition for these conditions with TKM. It is difficult to perform randomized controlled trials on people with disability. Therefore, large-scale observational and cohort studies should be conducted. We hope this study will help establish a suitable TKM policy for people with disabilities.